Analysing factors influencing the adoption of blockchain technology in maritime freight enterprises - Singh S.; Chakraborty K.; Pratap S.; Singh M.; Zhou F. (My University, 2025)
Maritime freight companies are beneficial in carrying the majority of commodities globally. The large number of parties involved makes data exchange hard. Blockchain technology’s potential benefits are becoming more apparent to maritime freight firms. This report examines the important factors influencing blockchain technology adoption in the maritime freight sector. To calculate their weights, the study applies the Grey-DEMATEL based Analytic Network Process. According to the analysis, the most important determinants are government policies, firm size, and perceived cost of investment. These insights can assist government agencies, freight companies, and blockchain service providers in planning successful implementations and increasing competitiveness. © 2024 Informa UK Limited, trading as Taylor & Francis Group.